Personal financial planning application - Kuak, Chun Pin (2024)
Personal financial planning is a strategic approach to achieving financial goals and improving various aspects of individuals' lives. The project's objective is to develop a Personal Financial Planning Application using Flutter, aimed at enhancing users' financial literacy and stability through effective money management and tailored suggestions for optimizing savings. The application not only encompasses essential functionalities but also introduces innovative features like a home screen widget, targeted expense tracking for specific events, and a dedicated saving function. Furthermore, the report addresses five key problem statements associated with the application's development and conducts an in-depth review of seven analogous systems to analyse their strengths, weaknesses, opportunities, and threats (SWOT analysis). Building upon this review, the report proposes solutions to overcome the identified limitations, thereby refining the project's approach. The proposed application encompasses four core modules: the report module, tracking module, saving module, and account module. These modules collectively ensure a comprehensive and user-friendly financial management experience. To achieve efficient development, the Rapid Application Development (RAD) methodology is chosen as the project's guiding approach. The primary coding languages for development are Flutter and Dart, enabling seamless cross-platform compatibility and robust functionality.